Symmetric Polynomials and Holomorphic Functions on Infinite Dimensional Spaces - Chernega, I. (Journal of Vasyl Stefanyk Precarpathian National University, 2015)
A survey of general results about spectra of uniform algebras of symmetricholomorphic functions and algebras of symmetric analytic functions of bounded type onBanach spaces is given